Dari Penjara ke Penjara: Perjuangan Bapak Pendiri Bangsa dalam Menjaga Nasionalisme - Selfi Mahat Putri (Proceeding International Conference on Malay Identity, 2022)
Abstract: The founding figures of the Republic, namely Soekarno, Hatta, Sjahrir, Tan Malaka, Agus Salim and many other important figures. Are elite people who fight for their nation. They not only struggled through the criticisms they gave to the colonialists, but they also felt that they were living in prison for the harsh criticisms they made against the colonial government. This they do in order to raise the spirit of their spirit of nationalism. Keyword: Prisons, Figure, Nasionalism